VENTRICULAR FREE WALL RUPTURE - Sahibzada, Palwasha; Ali, Niaz; Zahidullah, M.; Rehman, M. (Journal of Ayub Medical College Abbottabad, 2009)
Background: Left ventricular free wall rupture (FWR) is reported to occur in 2-6% of cases presenting with acute myocardial infarction. Mortality of this complication is very high, accounting for 20-30% of all infarct related deaths. The objective of our study was to present our surgical experience of free wall rupture over a period of five years from 2004-2009 Methodology: A review of our records over this period of time was undertaken. Results: In our series of six patients collected over this time period, three (50%) presented with hypotension and three (50%) with persistent chest pain. ECG evidence of myocardial infarction was present in 4 (67%) cases, LVH in 2 (33.3%) cases and 2 (33.3%) showed diffuse ST&T changes. Echocardiogram was useful in the diagnosis of rupture but was not confirmatory. Coronary angiography and left ventriculography was performed in all the patients. Surgery was performed in all cases confirming the FWR. Conclusion: In this small series there was no surgical mortality which may reflect the favourable prognosis in sub acute rupture where haemodynamic stability is achieved with medical therapy prior to surgery. Keywords: Free wall rupture, myocardial infarction, coronary artery bypass grafting